Mixed convection of MHD flow in nanofluid filled and partially heated wavy walled lid-driven enclosure - Öztop, Hakan Fehmi; Sakhrieh, Ahmad; Abu-Nadad, Eiyad; Al-Salem, Khaled (Pergamon-Elsevier Science Ltd, 2017)
A computational work has been done to investigate the effects of mixed convection of MHD flow in nanofluid filled and partially heated wavy walled lid-driven enclosure. Finite difference method is used to solve governing equations of mixed convection for different parameters as Hartmann number, Richardson number, nanoparticle volume rate in partially heated and wavy walled enclosure. It is found that the rate of heat transfer decreases with increasing the Hartmann number. The rate of heat transfer can be enhanced or reduced by increasing the volume fraction of nanoparticles based on Hartmann and Richardson numbers.
Keywords: Wavy walled cavity; Lid-driven flow; Nanofluids; Magnetic field; Partial heating